Fishermen’s Methods of Determining the Qibla Direction at Sea in the View of the Four Madhhabs - Ilmiyah, Ma’rifatul; Jannah, Elly Uzlifatul; Zhillah, Aufa Alfa (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Facing the Qibla to the Ka’bah in Makkah is one of the requirements for the validity of prayer for Muslims, including fishermen who are at sea. However, determining the direction of the qibla at sea can be challenging due to limited tools and the absence of a fixed reference point, such as a mihrab. This study aims to explore how fishermen in Paciran, Lamongan, determine the direction of the qibla while at sea, and to analyze this from the perspective of four schools of fiqh. This research is fieldwork conducted in Paciran, Lamongan. The primary data source is fishermen, while the secondary data sources are books, articles, research, and other writings related to the qibla. Data collection was carried out through interviews, observations, and documentation. The collected data is analyzed inductively. This research revealed that fishermen in Paciran use various methods to determine the direction of the qibla, including observing natural signs (sun, moon, and stars), using modern tools such as compasses, and following the guidance of the ship captain. From the perspective of the four schools of fiqh, the prayers performed by fishermen at sea are considered valid because they have made a sincere effort to face the qibla based on the principles of Islamic law, strong beliefs, and reasonable assumptions (dzan) regarding the direction they are facing. The study recommends that fishermen equip their boats with compasses to facilitate more accurate Qibla determination.